Factors affecting postdialysis fatigue among hemodialysis patients: a multi-group path analysis according to nutritional status - Zhang, Yuhan; Yang, Na; Bai, Xujiao; Liu, Yina; Li, Xiangyun; Yan, Meiqin; Liu, Yuxiang (Frontiers in Medicine, 2025)
PurposeThe aim was to investigate a structural postdialysis fatigue model, to verify the factors which affect the postdialysis fatigue of hemodialysis patients, and to evaluate the moderating effects of nutritional status on postdialysis fatigue through multi-group analysis.MethodsThis multicenter cross-sectional study was conducted in six blood purification centers across hospitals in Taiyuan, Shanxi, China, with a total of 1,281 hemodialysis patients recruited as participants. Data were collected using Pittsburgh Sleep Quality Index, Connor-Davidson Resilience Scale, The Social Support Rate Scale, Post-dialysis fatigue Questionnaire, The Simplified Nutritional Appetite Questionnaire, The Rome IV constipation diagnostic criteria. A multi-group structural equation modeling analysis was then conducted to test the moderating effect of nutritional status on postdialysis fatigue in hemodialysis patients.ResultsThe postdialysis fatigue model’s fit indices were adequate. Sleep quality, resilience and social support directly influenced postdialysis fatigue (β = 0.181, −0.322, −0.200, p < 0.01). Sleep quality, resilience and social support partial mediated constipation through postdialysis fatigue (β = −0.031, 0.038, 0.024, p < 0.01). Multi-group structural equation modeling did support the hypothesis of overall moderation by nutritional status, distinct patterns between the two groups were observed with respect to how background factors and interpersonal triggers related to postdialysis fatigue (Δχ2 = 28.879, 155.183, 205.135, 210.135, 230.285, Δdf = 6, 9, 11, 14, 17, p < 0.01). The magnitude of the direct effects of sleep quality and resilience on postdialysis fatigue was greater in hemodialysis patients with poor nutritional status (Critical ratios for difference = −1.958, −4.999).ConclusionSleep quality, resilience, social support can directly affect postdialysis fatigue, and can also indirectly affect constipation through postdialysis fatigue. Malnourished hemodialysis patients are more likely to suffer from poor sleep quality, psychological resilience and postdialysis fatigue. Vigorous efforts are needed to improve nutritional status in hemodialysis patients, which ultimately might improve postdialysis fatigue and constipation.